1990
DOI: 10.21273/jashs.115.6.884
|View full text |Cite
|
Sign up to set email alerts
|

Yield of Successively Cropped Polyethylene-mulched Vegetables as Affected by Irrigation Method and Fertilization Management

Abstract: Broccoli (Brassica oleracea L. var. italica), followed by tomato (Lycopersicon esculentum Mill) or squash (Cucurbita pepo L. var. melopepo), and then broccoli were produced in succession re-using the same polyethylene-mulched beds at two locations with different soil types. First-crop broccoli yield was earlier and greater with drip than with overhead irrigation and inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
2

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 2 publications
0
23
0
2
Order By: Relevance
“…The greater efficiency of water application and the ability to precisely deliver needed amounts of N to the crop root zone account for this. Reliable information for scheduling trickle irrigation is needed, along with guidelines for plant tissue testing for N. Several methods exist for scheduling trickle irrigation, including evapotranspiration (Clough et al, 1990;Hartz, 1993;McNeish et al, 1985), allowable soil water depletion (Bogle et al, 1989), and target soil water tensions (SWTs). The advantages of using target SWTs were discussed by Pier and Doerge (1995a).…”
mentioning
confidence: 99%
“…The greater efficiency of water application and the ability to precisely deliver needed amounts of N to the crop root zone account for this. Reliable information for scheduling trickle irrigation is needed, along with guidelines for plant tissue testing for N. Several methods exist for scheduling trickle irrigation, including evapotranspiration (Clough et al, 1990;Hartz, 1993;McNeish et al, 1985), allowable soil water depletion (Bogle et al, 1989), and target soil water tensions (SWTs). The advantages of using target SWTs were discussed by Pier and Doerge (1995a).…”
mentioning
confidence: 99%
“…Previous work found that on sandy soils, second and third crop yields increased with increasing rates of residual and concurrent N and K levels, and these yields were higher with concurrent than single fertilizer applications (4). Another study with cucurbits showed soluble salt levels and yields to be higher with split fertilizer applications (15).…”
Section: Introductionmentioning
confidence: 91%
“…Nitrogen was determined on ground tissue with 0.2 g aliquots by the complete combustion method (Dumas method) with a N analyzer (model CHN 600, LECO Corp., St. Joseph, MI). 4 MAYFIELD ET AL. 6 MAYFIELD ET AL.…”
Section: Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Double-cropping usually offers the potential to increase N efficiency in a multicrop sequence because the successive crops benefit from the residual N of the first crop (Clough et al, 1990;Kalmbacher et al, 1982). In the multicrop systems, supplemental N can be added by drip irrigation (Clough et al, 1990) or a liquid fertilizer injection wheel (Csizinszky et al, 1987).…”
Section: Concepts and Practices For Improving Nitrogen Management Formentioning
confidence: 99%